Circumferential excisions in the trunk and associations in ex-obese patients - José Carlos Daher; Daniel Augusto dos Santos Soares; Cesar Augusto Daher Ceva Faria; Bruno Peixoto Esteves; Ismar Ribeiro Junior; Luciano Gomes Moura; Leonardo Martins Costa Daher; Milena Carvalho Almeida Galdino (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Currently, obesity is a major problem. Changes in dietary habits, regular exercise and bariatric surgery promote better quality of life. Massive weight loss may cause deformities in different body segments, which are normally corrected in multiple surgeries. We present a systematic way of treating these patients, which enable surgical procedures in different regions of the body in a single step. METHODS: This was a retrospective observational longitudinal study. The surgical technique consisted of gull-wing type incision on the back with resection of fatty tissue associated with abdominoplasty that promoted improvements in the pubis, back, buttocks and lateral thighs via a single incision. The combination of satellite excision as the thigh lifting was associated in certain situations as well as treatment of the upper segment of the trunk in a second time. RESULTS: The age of patients ranged from 24 to 52 years, average of 34 years old. The mean surgical time in the circumferential excisions was 4 hours and 8 minutes. Surgical complications observed were hematoma, flap necrosis and/or infection. There were three cases of small dehiscence and seroma and one case of pulmonary thromboembolism. In the outpatient follow-up, 85.7% of patients showed to be very satisfied with the final result and no complaints about the size and position of scars. Technical analysis showed a satisfaction level of 92.8% of cases. CONCLUSION: Satisfactory results elucidated the safety and feasibility of the technique, and scars were acceptable due to significant improvement in body contouring.